La dictadura como sistema mítico‑ritual en la novela latinoamericana - Sawala, Wojciech (Romanica Silesiana)
The aim of this paper is to show that the novels El Señor Presidente (1946) by Asturias, El otoño del patriarca (1975) by García Márquez and La fiesta del Chivo (2000) by Vargas Llosa represent dictatorship as a mythical‑ritual system. The discourses the autocratic power creates and promotes, reveal mythological characteristics: atemporality, cult of personality and a manichaean genealogic narrative, all subjugated to the functional explanation‑legitimization axis. The latter should be understood — rather than in rational terms — as a performative action, which takes place via a ritual system, constantly re‑actualizing the original mythical narrative. The modalities of ritual we distinguish in the three texts are: tortures, national holiday and sexuality. All these activities — indistinctly if performed by the dictator himself or by his institutional machinery — reveal common characteristics, among which I stress the condition of ‘excess’ regarding their hypothetical pragmatic role. Key words: dictatorship novel, Latin America, mythical‑ritual system, excess